ANALISIS PENERAPAN GREEN PRACTICE RESTORAN STUJA COFFEE CIPETE - Thomas Sucipto; Stephanie Rosanto (JISOS: JURNAL ILMU SOSIAL, 2024)
This research investigates the implementation of Green Practice practices at the Stuja Coffee Cipete Restaurant with the aim of increasing understanding and knowledge of these practices. Qualitative verification methods were used with interviews and observations at Stuja Coffee. The research results show that Stuja Coffee needs to increase energy efficiency and use organic and seasonal ingredients. The SWOT analysis revealed a lack of education on environmentally friendly practices for employees and customers. However, this restaurant has the advantage of using environmentally friendly products and supporting environmental standards. The research results show that the percentage of implementing environmentally friendly practices at Stuja Coffee reached 52% overall. Recommendations include the continuation and development of environmentally friendly practices to achieve perfection. Increased education for employees and customers is needed. This research contributes to understanding the challenges and potential of environmentally friendly practices in the restaurant industry, while providing insight into the steps that Stuja Coffee and similar restaurants can take to increase the positive impact of their environmentally friendly practices